PENCEGAHAN DAN PENANGANAN KEMISKINAN MELALUI SUISTAINABLE DEVELOPMENT GOALS DI DESA TRUNAMANGGALA KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Sepian, Dhavif Maulana; Rizqy Maulana, Aldilla; Zaelani, Moch; Maulana, Adi; Nur Aini, Ani; Kuswandi, Aos; Ridwan (LPPM Universitas Islam 45 Bekasi, 2024)
Community service regarding education on preventing and handling poverty through a sustainable development goals approach, aims to provide understanding and strengthening to the community and Trunamangala Village officials in terms of preventing and handling poverty. As well as a commitment to implementing key performance indicators for extreme poverty literacy from the 2024 thematic real work lecture program and a form of commitment in efforts to achieve the 17 SDGs goals by 2030. The method used in this service activity is counseling provided by academics at the Islamic University 45 through community education to staff. village, the Village Consultative Body, and the Chair of the Rukun Warga and Rukun Tetangga as community representatives. The results of the service activities showed a positive and enthusiastic response from the community who took part in the counseling, this can be seen from the active participation of the community in listening to the outreach material as evidenced by the interactive discussions between the community and resource persons. Apart from that, at the end of this outreach activity, it succeeded in attracting participants to express their aspirations and receive appreciation from the village government